Bones of the lost [compact disc, unabridged] : a novel - Reichs, Kathy (Reichs, Kathy. Temperance Brennan series, 2013)
When Charlotte police discover the body of a teenage girl along a desolate stretch of two-lane highway, Temperance Brennan fears the worst. The girl's body shows signs of foul play. Inside her purse police find the ID card of a prominent local businessman, John-Henry Story, who died in a horrific flea market fire months earlier. Was the girl an illegal immigrant turning tricks? Was she murdered? Tempe soon finds herself at the center of a conspiracy that extends all the way from South America, to Afghanistan, and right to the center of Charlotte.